Street scenes in Hanchow. Part of a visit by a delegation of the Association des Amitiés Franco-Chinoises to China - Krauss, Christiana,
Street scenes in Hanchow. Part of a visit by a delegation of the Association des Amitiés Franco-Chinoises to China.